Antibacterial and Antibiofilm Activities of Chloroindoles Against Vibrio parahaemolyticus - Sathiyamoorthi, Ezhaveni; Faleye, Olajide Sunday; Lee, Jin-Hyung; Raj, Vinit; Lee, Jintae (Frontiers in Microbiology, 2021)
Vibrio parahaemolyticus is a food-borne pathogen recognized as the prominent cause of seafood-borne gastroenteritis globally, necessitating novel therapeutic strategies. This study examined the antimicrobial and antivirulence properties of indole and 16 halogenated indoles on V. parahaemolyticus. Among them, 4-chloroindole, 7-chloroindole, 4-iodoindole, and 7-iodoindole effectively inhibited planktonic cell growth, biofilm formation, bacterial motility, fimbrial activity, hydrophobicity, protease activity, and indole production. Specifically, 4-chloroindole at 20 µg/mL inhibited more than 80% of biofilm formation with a minimum inhibitory concentration (MIC) of 50 µg/mL against V. parahaemolyticus and Vibrio harveyi. In contrast, 7-chloroindole inhibited biofilm formation without affecting planktonic cell growth with a MIC of 200 µg/mL. Both chlorinated indoles caused visible damage to the cell membrane, and 4-chloroindole at 100 µg/mL had a bactericidal effect on V. parahaemolyticus within 30 min treatment, which is superior to the effect of tetracycline at the same dose. The quantitative structure-activity relationship analyses revealed that chloro and bromo at positions 4 or 5 of the indole are essential for eradicating the growth of V. parahaemolyticus. These results suggest that halogenated indoles have potential use in antimicrobial and antivirulence strategies against Vibrio species.